Media Gratis - Mirella, Doris (Canadian Journal of Optometry, 2021)
Media doesn't come free, ... or does it? To some extent, there are possibilities that are available for not-for-profit organisations, such as the Canadian Association of Optometrists (CAO). With ready media tools in one hand and a creative approach in the other, the National Public Education Committee (NPEC) has devised a number of different strategies to carry the momentum of the national paid media.